Bay' al-Murabahah: Mendudukkan Kembali Posisinya dalam Perbankan Syari’ah - Luhur Prasetiyo (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
Nowadays, Mura>bahah transaction becomes the most popular product which shari>’ah banking uses to sell its assets for amount of reasons. Total amount of shari>’ah banks store and transact their assets (fund) in mura>bahah system. The reason is that this product has not only small risk but also ease to manage related to muza>rabah and musha>rakah system. In the other hand, Many people don’t understand mura>bahah mechanism precisely. They often think that mura>bahah mechanism is as credit as well. It is, in fact, that mura>bahah system is a cash transaction which shari>’ah banks have. This paper is to elaborate mura>bahah system as a product of shari>’ah banking.